Impact of Leverage, Profitability, and Company Size on Tax Planning in Manufacturing Firms - Dwi Rahmawati, Yunita; Dilla Anggari Kholifami; Laras Safitri, Nadhila; Eko Satrio Wibowo, Hendrik; Pujiyantiningtyas, Vina; Amrulloh, Amri (Inovasi Analisis Data, 2024)
This research aims to examine the influence of leverage, profitability and company size on tax planning. The independent variables used in this research are leverage, profitability and company size. Meanwhile, the dependent variable in this research is tax planning. Tax planning in this research is measured by legal tax avoidance (Tax Avoidance) using Books Tax Difference (BTD). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2020-2022 period. Determining the sample in this research used the purposive sampling method. There are 37 manufacturing companies registered on the IDX which were used as research samples based on predetermined criteria. The research results show that leverage and profitability have a significant effect on tax planning. Meanwhile, size does not have a significant effect on tax planning